Association between Metabolic Components and Subclinical Atherosclerosis in Korean Adults - Hwang, In Cheol (The Korean Academy of Family Medicine, 2012)
BACKGROUND: Many studies have attempted to develop relatively simple and easy noninvasive measurements of atherosclerosis (NIMA), and each NIMA assesses different atherosclerotic properties. We, therefore, investigated the association between metabolic syndrome (MetS) components and different NIMAs. METHODS: This study included 1,132 Korean subjects over 20 years of age who had visited a Health Promotion Center in Korea. Carotid injury (increased carotid intima-media thickness or plaques) was evaluated by ultrasonography and arterial stiffness by brachial-ankle pulse wave velocity. The MetS components were assessed according to the Asian criteria of the American Heart Association/National Heart, Lung, and Blood Institute. RESULTS: Both arterial stiffness and carotid injury gradually deteriorated with increase in the number of MetS components. Arterial stiffness and carotid injury were associated with different MetS components, each of which had varying impact. After adjustment for all possible confounders such as age, sex, and lifestyle, elevated blood pressure (BP) was found to have the strongest association with arterial stiffness, whereas central obesity, impaired fasting plasma glucose, and elevated BP had comparable connection with carotid atherosclerosis. CONCLUSION: Individual MetS components were related with subclinical atherosclerosis in different ways. Elevated BP showed the strongest association with arterial stiffness, while central obesity, impaired fasting plasma glucose, and elevated BP showed good correlation with carotid atherosclerosis.